2002
DOI: 10.1191/0309132502ph389oa
|View full text |Cite
|
Sign up to set email alerts
|

From medical to health geography: novelty, place and theory after a decade of change

Abstract: In this paper, we reflect on the positioning of health geography within the wider academic landscapes of geography and health-related research. Drawing on examples from a number of countries, we consider the extent to which a ‘new geography of health’ has emerged in recent years. We structure our discussion around the themes of place, theoretical engagement and critical relevancy. Changes within the subdiscipline are placed in the context of a central question: what is new about the new geography of health?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
243
0
16

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 377 publications
(261 citation statements)
references
References 98 publications
2
243
0
16
Order By: Relevance
“…The social turn within medical geography (Smith and King, 2009;Smyth, 2008;Kearns and Moon, 2002;Hall, 2000) continued this interest, though bringing with it a renewed focus on individual's personal understandings of health and illness and how these understandings impacted on individuals' attitudes towards STIs and STI treatment facilities (Wilton, 1996).…”
Section: Geographical Research On Sexually Transmitted Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The social turn within medical geography (Smith and King, 2009;Smyth, 2008;Kearns and Moon, 2002;Hall, 2000) continued this interest, though bringing with it a renewed focus on individual's personal understandings of health and illness and how these understandings impacted on individuals' attitudes towards STIs and STI treatment facilities (Wilton, 1996).…”
Section: Geographical Research On Sexually Transmitted Infectionsmentioning
confidence: 99%
“…Young people who think that they might have an STI therefore sometimes prefer to attend community healthcare settings such as General Practices (GPs) for testing, where they can avoid the stigma associated with specialist STI treatment centres (Petersen et al, 2009;Goldenberg et al, 2008). However it is important to note that geographers have also shown that particular healthcare settings (even those associated with STIs) may have different meanings for the different individuals who use them (Rapport et al, 2009;Smyth, 2008;Downing, 2008;Kearns and Moon, 2002;Del Casino, 2001).…”
Section: Geographical Research On Sexually Transmitted Infectionsmentioning
confidence: 99%
“…The first of these concerned the object of study. Critics of a medical geography that was focussed on a largely descriptive spatial epidemiology sought to challenge and extend the focus of the subdiscipline by adopting the WHO conception of health, seen not merely as the absence of disease, but as related to broader definitions of well-being, inequity and social justice (Kearns 1993;Kearns and Moon 2002;Moss and Dyck 1996;Smith 1973;Smith 1994;Smith et al 2003). Researchers also directed attention to the processes and relations between places, health and health care, for example, through developing the concept of therapeutic spaces and landscapes (Conradson 2005;Gesler 1992Gesler , 2000Smyth 2005;Tonnellier and Curtis 2005;Williams 2007) or by giving value to experiential and emotionally inflected understandings of such relations (Anderson and Smith 2001;Atkinson and Farias 1995;Davidson et al 2005;Dyck 1992;Gesler and Kearns 2002;Milligan 2003;.…”
mentioning
confidence: 99%
“…What kind of knowledge should geographers pursue and with what imagined consequences and effects? Here, a divide emerged between those who positioned themselves as "policy-relevant" medical geographers through arguing that "real-world" and often quantitative data-sets were necessary to speak to and make an impact on policy (Dorling and Shaw 2002;Kearns and Moon 2002) and those who asserted that the more theoretical, emerging critical health geographies were important (Parr 2002) since "critical work which questions and contests the categories used in biomedical science has a clear and important role to play in medical geography's engagement with policy and debates around inequalities in health and health care -highlighting the processes by which some bodies are seen as more equal than others" (Evans 2006, 260).…”
mentioning
confidence: 99%
See 1 more Smart Citation